2019
DOI: 10.21859/ijb.2215
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Immune Response in Animal Model Using Recombinant Anti-NDV Vaccine

Abstract: Background Newcastle disease is a major avian disease that causes enormous economic loss in poultry industry. There have been a number of reports on the suitability of plant-based recombinant vaccine against this disease. Fusion (F) and hemagglutinin-neuraminidase (HN) epitopes of the Newcastle disease virus (NDV) represent the major immunogenic sites for development of recombinant anti-ND vaccines in plant hosts. Objectives The main objective of this research was to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, DIVA should be considered in the production of other subunit vaccines because of the obvious advantage it provides in segregating infected from vaccinated birds. Moreover, a group earlier expressed the F and HN epitopes of NDV in tobacco seedlings and demonstrated that the transgenic plant extract induced immune responses [168]. This suggests plants as useful vectors for epitope-based vaccines and could provide for the advantages of easy oral route vaccination and induction of mucosal immune response.…”
Section: Recent Advances In Nd Vaccine Developmentmentioning
confidence: 99%
“…However, DIVA should be considered in the production of other subunit vaccines because of the obvious advantage it provides in segregating infected from vaccinated birds. Moreover, a group earlier expressed the F and HN epitopes of NDV in tobacco seedlings and demonstrated that the transgenic plant extract induced immune responses [168]. This suggests plants as useful vectors for epitope-based vaccines and could provide for the advantages of easy oral route vaccination and induction of mucosal immune response.…”
Section: Recent Advances In Nd Vaccine Developmentmentioning
confidence: 99%
“…The NDV F protein expressed in staple crops like transgenic rice and corn was reported to induce the production of neutralizing antibodies in chickens challenged with a velogenic strain and provide similar survival rates as commercial LaSota vaccine based on the attenuated virus ( Guerrero-Andrade et al., 2006 ; Ma et al., 2020 ). Recombinant concatenated F and HN proteins were expressed in transgenic tobacco but unfortunately induced unideal production of antibodies in rabbits ( Shahriari et al., 2019 ).…”
Section: Plant-made Vaccines Against Viral Diseases In Farm Animalsmentioning
confidence: 99%
“…Another approach suggested the feasibility of producing concatenated F and HN epitopes without a genetic fusion to M protein in transgenic tobacco [ 94 ]. The authors established a DNA construct with four 96 base-pair tandem repeats of an HN epitope followed by three 153 base-pair tandem repeats of an F epitope.…”
Section: Pipeline For Production Of Plant-based Vaccinesmentioning
confidence: 99%
“…In follow-up studies, the authors reported that the transgenic plant extract was only moderately immunogenic in rabbits. Using ELISA, the transgenic plant extract was shown to induce lower production of anti-NDV antibodies in comparison to commercial NDV vaccines [ 94 ].…”
Section: Pipeline For Production Of Plant-based Vaccinesmentioning
confidence: 99%